Direct determination of Calcium in milk by atomic absorption spectrometry using flow-injection analysis - Petrovich, Marielsa Businaro; Amorim Filho, Volnei Resta; Gomes Neto, José Anchieta (Eclética Química, 2007)
A flow-injection system with sample and reagent addition by the synchronous merging zones approach for calcium determination in milk by flame AAS is proposed. Main parameters were optimized using a factorial design with central point. The optimum conditions were 2.5% (m/v) for La concentration, 8 mL min -1 for the carrier flow-rate, 20 cm for coiled reactor and 250 ìL for sample volume. Different sample preparation procedures were evaluated such as dilution in water or acid and microwave-assisted decomposition using concentrated or diluted acids. The optimized flow system was applied to determine Ca in eleven commercial milk samples and two standard reference materials diluted in water. Similar calcium levels were encountered comparing the results obtained by the proposed method (dilution in water) with those obtained using microwave-oven digestion. Results obtained in two standard reference materials were in agreement at 95% confidence level with those certified. Recoveries of spiked samples were in the 93% - 116% range. Relative standard deviation (n = 12) was < 5.4% and the sample throughput was 150 measurements per hour, corresponding to a consumption of 250 μL of sample and 6.25 mg La per determination.